Carvedilol delays the progression of small oesophageal varices in patients with cirrhosis: a randomised placebo-controlled trial. Issue 10 (13th June 2016) - Bhardwaj, Ankit; Kedarisetty, Chandan Kumar; Vashishtha, Chitranshu; Bhadoria, Ajeet Singh; Jindal, Ankur; Kumar, Guresh; Choudhary, Ashok; Shasthry, S M; Maiwall, Rakhi; Kumar, Manoj; Bhatia, Vikram; Sarin, Shiv Kumar
Abstract : Background and aims: Carvedilol is effective in the primary prophylaxis for large oesophageal varices. We investigated its use in preventing progression of small to large oesophageal varices. Methods: Consecutive cirrhotics with small oesophageal varices were prospectively randomised to either carvedilol (n=70) or placebo (n=70) and followed up for a minimum of 24 months. Endoscopy was done at baseline and six monthly intervals. Hepatic vein pressure gradient (HVPG) was measured at baseline and at 12 months. The primary endpoint was development of large varices. Results: Baseline characteristics in two groups were comparable. The predominant aetiology of cirrhosis was non-alcoholic fatty liver disease in both the groups. The mean dose of carvedilol administered was 12±1.67 mg/day and the target heart rate achieved was 58±3 bpm. A higher proportion of patients in carvedilol group had non-progression to large varices than placebo (79.4% vs 61.4%; p=0.04); the mean time of non-progression to large varices was 20.8 months (95% CI 19.4 to 22.4) in carvedilol group and 18.7 months (95% CI 17.1 to 20.4) in placebo group (p=0.04). There was a modest reduction of HVPG at 1 year in carvedilol group (−8.64%) compared with placebo (+0.33%) (p=0.22). None of the patients in either group died of variceal bleeding or liver-related causes. No major adverse events were observed in either group. Conclusions: Carvedilol is safe and effective in delaying the progression of small to large oesophageal varices in patients with cirrhosis. Trial registration number: NCT01196507; post-results.